2005
DOI: 10.1074/jbc.m505014200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Consequences of Hypertrophic and Dilated Cardiomyopathy-causing Mutations in α-Tropomyosin

Abstract: To study the functional consequences of various cardiomyopathic mutations in human cardiac ␣-tropomyosin (Tm), a method of depletion/reconstitution of native Tm and troponin (Tn) complex (Tm-Tn) in cardiac myofibril preparations has been developed. The endogenous Tm-Tn complex was selectively removed from myofibrils and replaced with recombinant wild-type or mutant proteins. Successful depletion and reconstitution steps were verified by SDS-gel electrophoresis and by the loss and regain of Ca 2؉ -dependent reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
61
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 39 publications
(40 reference statements)
12
61
2
Order By: Relevance
“…The pCa 50 and cooperativity values from our ATPase and ANS fluorescence assays using RTFs containing WT Tm were consistent with those of previous studies (24,33), but were different between the two assays (Tables 3 and 4). These differences in WT parameters (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…The pCa 50 and cooperativity values from our ATPase and ANS fluorescence assays using RTFs containing WT Tm were consistent with those of previous studies (24,33), but were different between the two assays (Tables 3 and 4). These differences in WT parameters (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…This finding implies that L29Q may decrease the Ca 2+ sensitivity and disrupt the signal from the phosphorylated cTnI to cTnC. However, this finding contradicts other reports of FHC mutations generally having higher myofilament Ca 2+ sensitivities (Chang et al, 2005;Karibe et al, 2001). Recent NMR and ultraviolet/visual spectrum titration studies showed that L29Q essentially has the same Ca 2+ affinity as that of wild-type cTnC (Baryshnikova et al, 2008) although this technique presents challenges for measuring Ca 2+ affinity (see below).…”
Section: In Vitro Analyses and Human Cardiac Tnc Mutation Studiescontrasting
confidence: 54%
“…Several groups have postulated that myofilament Ca 2ϩ sensitivity is the underlying mechanism of these cardiomyopathies. In fact, it has been hypothesized that all FHC-associated tropomyosin and troponin mutations increase myofilament sensitivity, and, conversely, dilated cardiomyopathy-associated mutations are associated with decreased Ca 2ϩ sensitivity (8,19,20), however, these relationships remain controversial. In addition, mutations in other sarcomeric proteins, such as the regulatory myosin light chain (E22K), which are associated with FHC, have frequently been shown to increase the Ca 2ϩ sensitivity of force generation (39).…”
mentioning
confidence: 99%